Pembatalan Perkawinan yang Tertolak Sebab Kawin Paksa Menurut Hukum Islam - Dermawan, Gineng Putri; Murniati (El 'Ailaah, 2026)
Marriage should be established on the basis of mutual consent between both parties in order to prevent the occurrence of forced marriage. In Islamic law, the willingness of both spouses is a fundamental element and a requirement for the validity of a marriage. However, there was a petition for marriage annulment submitted to the Bandung Religious Court which was rejected by the judge, despite the Petitioner’s claim that the marriage took place under coercion. This Islamic legal perspective on the research judge’s aims decision to in examine case the Number 2860/Pdt.G/2023/PA.Badg concerning the rejection of marriage annulment due to forced marriage. The research method employed in this study is a qualitative approach using a combination of library research and field research. The data collection techniques used include The findings of this study structured reveal interviews that the and documentation. Bandung Religious Court judge’s decision to reject the petition for marriage annulment in case Number 2860/Pdt.G/2023/PA.Badg was based on the Petitioner’s inability to provide sufficient evidence for the claims. Furthermore, the judge’s decision is in accordance with Islamic law, since the marriage in question fulfilled the pillars and legal requirements of marriage, namely the presence of mutual consent from both spouses.